New geochronological constraints for the Upper Cretaceous Nenjiang Formation in the Songliao Basin, NE China. (October 2019) - Yu, Zhiqiang; He, Huaiyu; Deng, Chenglong; Xi, Dangpeng; Qin, Zuohuan; Wan, Xiaoqiao; Wang, Chengshan; Zhu, Rixiang
Abstract: The Nenjiang Formation in the Songliao Basin, northeastern China, is of great significance because it records a series of geological, geodynamical and paleoenvironmental events, such as lake transgression events, lake anoxic events, sea water incursion events, Cretaceous Normal Superchron, and important stratigraphic boundaries. Here we report a chronology for the non-marine Upper Cretaceous Nenjiang Formation based on secondary ion mass spectrometry (SIMS) U–Pb zircon analyses from the east borehole of the Cretaceous Continental Scientific Drilling and two outcrop sections, which are located in different structural provinces of the Songliao Basin. Stratigraphic correlation between the borehole sequence and the exposed outcrop sections is achieved by combining lithostratigraphy, biostratigraphy, and SIMS U–Pb zircon geochronology. Two bentonite layers are recognized in the Nenjiang Formation: the older occurs at the formational contact between the Yaojia and Nenjiang Formations; the younger occurs between Members 1 and 2 of the Nenjiang Formation. SIMS U–Pb zircon dating yields ages of 85.1–85.2 Ma and 83.0–83.3 Ma, respectively, representing ages of the boundaries of the Yaojia/Nenjiang Formations and Members 1/2 of the Nenjiang Formation, as well as ages of lake transgression events and associated lake anoxic events, and two of the sea water incursion events. Furthermore, the age of Cretaceous Normal Superchron termination can be estimated at 82.5–82.8 Ma.